Price formation and real estate characteristics : residential Real Estate, Lisbon – Portugal - Vaz, António Jorge Ferreira (2012)
The discretionality and the appraisers’ subjectivity that characterize traditional real estate valuation are still allowed to take part in the formation of the asset price even when respecting international standards (EVS, IVS) or Appraisal Institution´s regulations (TEGOVA, RICS, etc.). The application of Econometric Methods to real estate valuation by the use of statistic procedures aims at the elimination of subjectivity on the appraisal process. On this study, Hedonic Models (Econometric Methods applied to Real Estate Appraisal) are used to determine the most important characteristics that define the multifamily residential real estate selling price and therefore to make estimations on real estate selling price (knowing the asset characteristics). Two different Statistical Techniques were used in order to compare the results: Multiple Lineal Regression; and Factorial Analysis. These techniques were applied to a sample of 82 flats for sale located in Lisbon, Portugal. From the 15 studied characteristics, we conclude that the ones the ones that determine/influence the most the asset price are: Area (m2); Nr. of Bathrooms; Privileged View; Nr. of Parking places. Using these 4 variables the asset’s price estimation model obtained explains 80, 9% of the Real Estate selling Price.